Социально-классовые характеристики политической культуры в Украине: опыт применения социологического теста "Типы политической культуры" - Щербак, М. (Социология: теория, методы, маркетинг, 2006)
This article covers the basic changes in the social class distinctive features of the political
culture of Ukrainian society, which can be revealed with the help of integral test of the
types of political culture. The Ukrainian scientists pioneered the above mentioned
procedure combining various theoretical approaches that had been developed by now
and using an original approach to the typology of political culture, which takes into
account the main aspects of its formation in the transitional period of Ukrainian society.